HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KEINGINAN UNTUK SEMBUH PADA PENYALAHGUNA NAPZA DI LEMBAGA PEMASYARAKATAN WIROGUNAN KOTA YOGYAKARTA - Isnaini, Yulia; Hariyono, Widodo; Utami, Isti ken (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: The growth and developed hospital should be effectively and efficiency managed. This fact should be carried out in order to face strict competitions in the health world. The hospital can survive in facing the existing competitions by counting the previous hospital fee and using fee account model competitively. In PKU Muhammadiyah Unit I Yogyakarta, Set of Essential Services (SES) of caesarea operation fee, class III, and cost sharing between the hospital and the goverment are different. In this study, the researcher only counts caesarea operation fee for re-use in order to create low cost sharing. Up till now, the hospital party never counts those existing differences. This case will lead them to get a financial loss. By having this fact, the researcher was eager to know about cost sharing analysis of caesarea operation fee account, class III, in PKU Muhammadiyah Unit I Yogyakarta.Methode: This was qualitative descriptive research which analyses the exact fee by using real cost method to know the difference of patient?s fee toward the real fee in the hospital. Bisides that, interview method was applied to know the head of finance and Central Surgeon Installation (CSI) workers opinion.Resulth: The result of Set of Essential Services (SES) fee of health insurance? toward caesarea operation was Rp 1.230.429, caesarea operation fee by using real cost method was Rp 3.764.388, in fact, the exact fee from RS PKU Muhammadiyah Unit I Yogyakarta was Rp 4.705.388. In conclusion, the final results were the difference of Set of Essential Services (SES) fee of health insurance between real cost was Rp 2.533.959 and the difference of Set of Essential Services (SES) fee of health insurance? between the exact hospital costs was Rp 3.475.056.Conclusion: The researcher has concluded that set of costs which is based on unit cost was higher that hospital cost recently. The highest cost was given for buying medicines and temporary materials. The hospital party has to decide the best strategy to reduce those differences.Key words: cost sharing, real cost method, Set of Essential Services (SES) of caesarea operation fee, class III.